AWAKEN-Ing a New Frontier in Neonatal Nephrology - Askenazi, David Joseph (Frontiers in Pediatrics, 2020)
In 2013, literature about the epidemiology of neonatal acute kidney injury (AKI) was limited to primarily retrospective, single center studies that suggested that AKI was common and that those with AKI had higher rates of mortality. We developed a 24-center retrospective cohort of neonates admitted to the NICU between January 1 - March 31, 2014. Analysis of the Assessment of Worldwide Acute Kidney Epidemiology in Neonates (AWAKEN) cohort, has allowed describe the prevalence, risk factors and impact of neonatal AKI for different gestational age cohort. The ample sample size allows us to provide convincing data to show that those with AKI have an increase independent higher odds of death and prolonged hospitalization time1. This data mirrors similar studies in pediatric2 and adult3 critically ill populations which collectively suggest that patients do not just die with AKI, but instead, AKI is directly linked to the hard clinical outcomes. This study has allowed us to answer multiple other questions in the field which has expanded our understanding of the risk factors, complications, impact of fluid overload, the neonatal AKI definition and suggests interventions for improving outcomes. Furthermore, we it has brought together neonatologist and nephrologist within and across centers. Finally, the AWAKEN project has enabled us to build relationships and infrastructure that has launched the Neonatal Kidney Collaborative http://babykidney.org/on its way to accomplish its stated mission to improve the health of newborns with or at risk for kidney disease through multidisciplinary collaborative research, advocacy, and education.